Constraining the Milky Way halo potential with the GD-1 stellar stream. Issue 3 (13th April 2019) - Malhan, Khyati; Ibata, Rodrigo A
Abstract: We use ESA/ Gaia astrometry together with SEGUE and LAMOST measurements of the GD-1 stellar stream to explore the improvement on the Galactic gravitational potential that these new data provide. Assuming a realistic universal model for the dark matter halo together with reasonable models of the baryonic components, we find that the orbital solutions for GD-1 require the circular velocity at the Solar radius to be V_circ(R_) =244± 4 km s^-1, and also that the density flattening of the dark halo is q_ρ =0.82^+0.25_-0.13 . The corresponding Galactic mass within 20 kpc was estimated to be M_MW(20 kpc)=2.5± 0.2 × 10^11 M_ . Moreover, Gaia 's excellent proper motions also allowed us to constrain the velocity dispersion of the GD-1 stream in the direction tangential to the line of sight to be 2.30 km s^-1 (95 per cent confidence limit), confirming the extremely cold dynamical nature of this system.